A systematic review on clinical effectiveness, side-effect profile and meta-analysis on continuation rate of etonogestrel contraceptive implant - Kusum V. Moray; Himanshu Chaurasia; Oshima Sachin; Beena Joshi (BMC, 2021)
Abstract Background Unintended pregnancies (UIP) have a significant impact on health of women and the health budget of countries. Contraception is an effective way to prevent UIPs. The study objective was to collate evidence on clinical effectiveness of etonogestrel subdermal implant (ESI), continuation rate and side effect profile among eligible women of reproductive age group, as compared to levonorgestrel intrauterine system (LNG-IUS), copper intrauterine device (Cu-IUD) and depot medroxy progesterone acetate injections; other types of contraceptive implants were excluded as comparators. Methods The protocol of the systematic review was registered in Prospero (registration number: CRD42018116580). MEDLINE via PubMed, Cochrane library and web of science were the electronic databases searched. A search strategy was formulated and studies from 1998 to 2019 were included. Clinical trial registries and grey literature search was done. Critical assessment of included studies was done using appropriate tools. A qualitative synthesis of included studies was done and a meta-analysis was conducted in RevMan software for continuation rates of ESI as compared to other long acting reversible contraceptives (LARC) e.g. LNG IUS and Cu-IUD. Results The search yielded 23,545 studies. After excluding 467 duplicates, 23,078 titles were screened and 51 studies were included for the review. Eight of the 15 studies reporting clinical effectiveness reported 100% effectiveness and overall pearl index ranged from 0 to 1.4. One-year continuation rates ranged from 57-97%; 44-95% at the end of second year and 25-78% by 3 years of use. Abnormal menstruation was the most commonly reported side effect. There was no significant difference in bone mineral density at 1 year follow-up. The meta-analyses showed that odds ratio (OR) of 1-year continuation rate was 1.55 (1.36, 1.76) for LNG-IUS vs. ESI and 1.34 (1.13, 1.58) for copper-IUD vs. ESI; showing that continuation rates at the end of one-year were higher in LNG-IUS and copper-IUD as compared to ESI. Conclusion ESI is clinically effective and safe contraceptive method to use, yet 1-year continuation rates are lower as compared to LNG-IUS and copper-IUD, mostly attributed to the disturbances in the menstruation.